COVID-Subsidiarity as A New Political Phenomenon - S. P. Arteev (Vestnik MGIMO-Universiteta)
The COVID-19 pandemic has rapidly and synchronously changed the lives of billions of people all over the planet. The economic, social, and political problems were entwined in tight contradictions. The impact of the COVID-19 pandemic on international and national political issues has been the focus of attention of academia around the world since early 2020. The primary attention has been focused on international and national levels. At the same time, the subnational and local dimensions of the corona crisis "elude" the political science community. Nevertheless, fighting against the new biogenic danger changes the redistribution of power between the national, subnational, and local levels. The article analyses this redistribution and presents its preliminary due to the incompleteness of the pandemic results. It seeks to identify the main patterns of a new round of the evolution of subsidiarity associated with the COVID-19 pandemic. What role does COVID-subsidiarity play now, and what are its prospects in the post-pandemic world? The article employs the concept of megatrends and comparative methods to answer this question. The results show that extraordinary powers have been redistributed worldwide from the national to the subnational level. The essential characteristic of COVID-subsidiarity is the emergence of emergency powers at the subnational and local levels. It happens in states with different political regimes and different political cultures. It is likely that even after the end of the current pandemic, in some cases, the subnational regions will try to retain the expanded powers they acquired during the emergency. This is part of a broader process of transformation of the modern state and its adaptation to the newly emerging political organization of the world.